O processo de criação da reserva extrativista marinha do litoral sul de Sergipe : embates e limites - Gonçalves, Fernanda Damaceno Silva (2015)
It‟s in process in the competent instances the solicitation of creation of the Marine Extractive Reservation located at southern coast of Sergipe. That new proposal has being articulated by different social actors, with several interests of appropriation, control and use of the natural resources of the area in question. The conflicts observed in the studied area will probably be in evidence in the creation of RESEX and are mostly related to the lack of articulation between the actors, by the the real state speculation and turism. On the other hand there is the local tradicional population who claim the right to keep using the natural resources as subsistence source. Thereby the reserach had as main purpose to analise the specificity of the environmental conflicts in the creation of this new proposal seeking to understand the relation and positioning of the social actors involved in the conflicts related to the process of creation of southern coast RESEX and change of trading of the category since that today the same area is an Ambiental Protection Area.